Effects of diazepam, ketamine HCl and sevoflurane anesthesia on vital and recovery values of nine long legged buzzards (Buteo rufinus) upon wing amputation - İŞLER, C. T.; ALTUĞ, M. E.; YURTAL, Z.; DEVECI, M. Z.Y. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this clinical study, effects of diazepam + ketamine HCl + sevoflurane anesthesia on vital functions and recovery duration and qualityofnine long legged buzzards were evaluated upon wing amputation. Operation was decided for long legged buzzards and heartand breathingrate, body temperature, and reflexes of long legged buzzards were evaluated before, during and after the anesthesia. Diazepam and ketamine HCl injection increased the heart rate whereas it was decreased by sevoflurane. Respiratory rate decreased upon sevoflurane application. Body temperature decreased during anesthesia. Recovery began in the 3rd minute after cessation of sevoflurane administration with return of eye reflexes and completedin the 35th minute. It was observed that although birdsrecovered from anesthesia, danger of hypothermia persisted for a long time.There was a significant difference between the respiratory and heart rates during the ketamine HCl and sevofluraneanesthesia from those in the preoperative period. However, there was no statistically significant difference between pre and post operative periods in terms of vital parameters. For the first time, effects of diazepam + ketamine HCl + sevoflurane anesthesia combination on vital parameters are evaluated in long legged buzzards in Turkey.